(untitled) (Tanzania Medical Journal, 2022)
Background Neural tube defects (NTDs) are severe congenital anomalies of the central nervous system. The specific cause is not known, though several factors including gene variants involving the folate metabolism have been implicated in the etiology. This study aimed at identifying the gene expression profile of selected genes known to be associated with NTDs among infants attending Muhimbili National Hospital (MNH) and Muhimbili Orthopaedic Institute (MOI). Methods We conducted a matched case control study involving infants who were attending MNH and MOI during 6 months of the study period. Each case was matched with two controls by gestational age, sex and birth weight. Whole blood samples were collected from all study participants for genetic analysis. Total RNA was isolated using Qiagen RNA blood mini kit, and reversed transcribed into complementary DNA (cDNA) using Super Script II Reverse Transcriptase cDNA Synthesis kit. Real-time polymerase chain reaction was performed on extracted cDNA by a Light Thermal Cycler 480 machine using specific primers for studied genes to determine their expression levels. Results were analysed by GraphPad Prism 5 Software, using Student t-test, and Bonferroni post hoc statistical tests. A p value of < 0.05 was considered to be statistically significant. Results The study recruited 50 cases and 100 controls. Among eight studied genes, we found significantly low expression of Methylenetetrahydrofolate reductase [MTHFR] gene among cases than controls (p=0.006). Expression of others genes were having variations and expressed at very low levels in both cases and controls. Conclusion A low expression level of MTHFR gene was a significant risk factor for the occurrence of NTDs amongst infants attending MNH and MOI. We recommend further DNA sequencing studies to determine exact genetic mutations that affect the low expression of MTHR gene amongst infants with NTDs in our setting.